Are PTTG1 variants associated with tumor characteristics and p53/Ki-67 expression in pituitary neuroendocrine tumors - Baikstiene, Ieva; Duseikaite, Monika; Vilkeviciute, Alvita; Juskiene, Martyna; Makstiene, Jurgita; Poskiene, Lina; Tamasauskas, Arimantas; Verkauskiene, Rasa; Liutkeviciene, Rasa; Zilaitiene, Birute (Frontiers in Endocrinology, 2026)
BackgroundPituitary tumor-transforming gene 1 (PTTG1) is a proto-oncogene implicated in pituitary neuroendocrine tumors (PitNETs) pathogenesis through regulation of the cell cycle, genomic instability, and angiogenesis. Overexpression of PTTG1 promotes tumor growth, but the impact of its genetic variants in PitNETs size is insufficiently defined.ObjectiveTo evaluate the impact of PTTG1 gene variants (rs1895320, rs2910200, and rs6882742), circulating PTTG1 levels, and immunohistochemical markers (Ki-67 and p53) on PitNETs susceptibility and clinical features.Methodscase–control study included patients with PitNETs and age- and gender-matched controls. Diagnosis of PitNETs was confirmed by MRI/CT and/or histopathology. Genomic DNA was extracted from peripheral blood, and three PTTG1 variants (rs1895320, rs2910200, rs3811999) were genotyped using TaqMan® real-time PCR assays. Serum PTTG1 levels were measured by ELISA, while Ki-67 and p53 expression were assessed immunohistochemically with digital image analysis. Statistical analyses included chi-square comparisons of genotype/allele distributions, logistic regression for PitNETs risk (odds ratios, 95% CI), and nonparametric tests for biomarker evaluation.ResultsA total of 340 participants were enrolled, comprising 120 PitNET patients and 220 controls. Median age (53.5 vs. 54 years) and gender distribution did not differ between the groups. Among patients, 35% had microadenomas and 65% had macroadenomas. Logistic regression revealed that the PTTG1 rs3811999 TT genotype was associated with increased odds of microadenoma occurrence (OR = 2.53, 95% CI: 1.17-5.48, p = 0.018). The PTTG1 rs2910200 TT genotype and T allele were significantly more common in tumors with lower proliferative activity Ki-67 LI < 3% (p = 0.013 and p = 0.004), suggesting a potential association with reduced proliferation. In contrast, the rs3811999 TT genotype and T allele were more frequent in tumors with Ki-67 LI > 3% (p = 0.015 and p = 0.011), indicating a relationship with higher proliferative potential. Macroadenomas exhibited significantly higher p53 H-scores than microadenomas (27.34 vs. 16.00, p = 0.012), while no associations were observed with gender, invasiveness, activity, or recurrence.ConclusionsResults suggest that PTTG1 rs3811999 may influence tumor size or growth pattern, possibly contributing to early tumorigenesis. We can hypothesize that the variant may alter gene expression or protein function, thereby predisposing to PitNETs development at an earlier stage (microadenomas). Future research should integrate molecular studies with larger genetic datasets to clarify how PTTG1 variants contribute to PitNETs’ pathophysiology.